DEMOCRACY, GLOBALIZATION AND LEGAL REGULATION: THE RELATIVIZATION OF SOVEREIGNTY AND THE EFFECTIVENESS OF FUNDAMENTAL RIGHTS - Mateus de Oliveira Fornasier; Gilmar Antonio Bedin; Aline Michele Pedron Leves (Revista Eletrônica do Curso de Direito da UFSM, 2019)
Democracy as a form of society isn’t a recent innovation of humanity. The current problem lies in the fact that, with the world phenomenon of globalization and the impact of new technologies, it was verified a real omnipresence of a weakening of democratic regimes in the contemporary scenery. In front of the massive global techno-scientific development, it is sought to understand how the horizontal effectiveness of fundamental rights can contribute with contemporary democracies, which pass to be evidenced on a low scale in the political game. Notably, the financial system makes reason a priority, and the notion of search for promotion of fundamental rights is confused with the States’ search for greater economic power. Thus, this study aims to analyze, using hypothetical-deductive method and bibliographical research technique, the current paradigm for the realization of an ideal of democracy that guarantees the protection of fundamental rights in face of fast techno-scientific advances in globalized society.